Fear God and walk humbly : the agricultural journal of James Mallory, 1843-1877 - Mallory, James, 1807-1877.; McWhiney, Grady; Moore, Warner O.; Pace, Robert F. (Tuscaloosa : University of Alabama Press, 1997)
Mallory's journal spans three major periods of the South's history - the boom years before the Civil War, the rise and collapse of the Confederacy, and the period of Reconstruction after the Civil War. Mallory's interests were varied and wide ranging, but weather and agriculture dominate his journal, for agriculture was his passion. A member of the Alabama Agricultural Society, he encouraged efforts to improve. His journal describes the vicissitudes of raising and marketing various crops and animals. Concerns with cotton, corn, wheat, other grains, livestock, orchards, unusual farming methods, fertilizers, and experiments all receive comment.
Includes index.
Print version record.
Keywords: Mallory, James, -- 1807-1877 -- Diaries; Mallory, James, -- 1807-1877; Talladega County (Ala.) -- Social life and customs; Farm life -- Alabama -- Talladega County; Farmers -- Alabama -- Talladega County -- Diaries; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- State & Local -- General; Farm life; Farmers; Manners and customs; Alabama -- Talladega County; Landbouw; Dagelijks leven; Nieuws; Weer; Alabama; Electronic book; Electronic books; Diaries; Dagboeken (vorm)